Exploratory study of hospital abortion. Analysis of 100 cases of abortion treated in a continuous series in Enrique Sotomayor Maternity Clinic in Guayaquil - Serrano Gómez, César (2015)
A study of 100 cases of abortion is performed in a maternity clinic, by using a questionnaire. The most interesting finding was the high fertility in women treated for abortion, rejection by the unlimited fertility preference for small family and a reduced use of modern contraceptive methods. A provisional estimate of the cost of abortions spending reveals a close to 13% of the budget of the institution.